2021
DOI: 10.1007/s10904-021-01994-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electrical and Optical Properties of PVC/ZnTe Nanocomposite Thin Films

Abstract: ZnTe nanoparticles (NPs) were synthesized using hydrothermal method and then were dispersed in poly(vinyl-chloride) (PVC) to prepare hybrid PVC/ZnTe nanocomposite thin films which were deposited on glass substrates by the dip coating technique. Structural, optical and electrical properties of films were investigated by different techniques. XRD analysis revealed that synthesized ZnTe NPs have a cubic structure and a nanoscale size,while pure PVC films have a weak degree of crystallinity and exhibit a broad dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The broad starching vibration of the -OH groups is observed at 3459 cm −1 . The band at 2361 cm −1 is related to CO 2 from the atmosphere [28]. The band at 1746 cm −1 is attributed to the C=O bond [34] which shifted from its position to lower wavenumber at ∼ 1741, 1735, and 1740 cm −1 for 1%, 2%, and 3% CdSSe-PVC films, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The broad starching vibration of the -OH groups is observed at 3459 cm −1 . The band at 2361 cm −1 is related to CO 2 from the atmosphere [28]. The band at 1746 cm −1 is attributed to the C=O bond [34] which shifted from its position to lower wavenumber at ∼ 1741, 1735, and 1740 cm −1 for 1%, 2%, and 3% CdSSe-PVC films, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, El-Hachemi et al [28] reported a PVC system reinforced with different concentrations of ZnTe nanoparticles and found that the optical properties of the prepared system improved with increasing the ZnTe concentration in the matrix. Rouabah et al [23] investigated the PVC-CdS system's the optical properties and concluded that the PVC-CdS films are transparent in visible-light, besides tuning the optical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that the FL intensity is small for λ exc = 317 nm and highest for λ exc = 380 nm. The characteristic emission band of PVC excimer fluorescence corresponding to electronic π*–π transition 71 appeared at 395 nm for excitation λ exc = 317 nm and shifted to 408 and 468 nm for λ exc = 380 and 434 nm excitation wavelengths. The shoulder peaks appearing right to the main band may be assigned to π*–n transition or trapped energy levels resulting from impurities defects 71 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic emission band of PVC excimer fluorescence corresponding to electronic π*–π transition 71 appeared at 395 nm for excitation λ exc = 317 nm and shifted to 408 and 468 nm for λ exc = 380 and 434 nm excitation wavelengths. The shoulder peaks appearing right to the main band may be assigned to π*–n transition or trapped energy levels resulting from impurities defects 71 . The small emission peak at 570 nm, Figure 10B, appeared only for high NiO content and assigned to NiO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation